MBD1 and MeCP2 expression in embryos and placentas from transgenic cloned goats. Issue 4 (3rd July 2017) - Jia, Ruoxin; Zhang, Guomin; Fan, Yixuan; Zhou, Zhengrong; Wan, Yongjie; Zhang, Yanli; Wang, Ziyu; Wang, Feng
Summary: DNA methylation is an important form of epigenetic regulation in mammalian development. Methyl-CpG-binding domain protein 1 (MBD1) and methyl-CpG-binding domain protein 2 (MeCP2) are two members of the MBD subfamily of proteins that bind methylated CpG to maintain the silencing effect of DNA methylation. Given their important roles in linking DNA methylation with gene silencing, this study characterized the coordinated mRNA expression and protein localization of MBD1 and MeCP2 in embryos and placentas and aimed to analysis the effects of MBD1 and MeCP2 on transgenic cloned goats. Our result showed that MBD1 expression of transgenic cloned embryo increased significantly at the 2–4-cell and 8–16-cell stages ( P < 0.05), then decreased at the morula and blastocyst stages ( P < 0.05); MeCP2 expression in transgenic cloned embryo was significant decreased at the 2–4-cell stage and increased at the 8–16-cell stage ( P < 0.05). Placenta morphology analysis showed that the cotyledon number of deceased transgenic cloned group (DTCG) was significantly lower than that the normal goats (NG) and in the live transgenic cloned goats (LTCG) ( P < 0.05). MBD1 and MeCP2 were clearly detectable in the placental trophoblastic binucleate cells by immunohistochemical staining. Moreover, MBD1 and MeCP2 expression in DTCG was significant higher than in the NG and the LTCG ( P < 0.05). In summary, aberrant expression of methylation CpG binding proteins MBD1 and MeCP2 was detected in embryonic and placental development, which reflected abnormal transcription regulation and DNA methylation involved in MBD1 and MeCP2. These findings have implications in understanding the low efficiency of transgenic cloning.